Função de resposta do meloeiro a doses de adubaçã o nitrogenada para dois níveis de irrigação - Soares, Cristiana Araújo [UNESP]; Rocha Jr., Agenor Francisco; Da Silva, Natália Soares; Mousinho, Francisco Edinaldo Pinto; Zanini, José Renato [UNESP] (My University, 2013)
With this research was evaluated the response of the melon to the application of nitrogen fertilizer levels, to two irrigation levels. The same was donein the experimental area of Teresina Agricultural College, affiliated with the Federal University of Piauí in Teresina, PI, Brazil. It was used a randomized block design with four replications and four doses of nitrogen (0, 75, 150 and 300kg Nha-1), using two irrigation levels equivalent to 1 and 1.5 times the crop evapotranspiration (ETc). For each level of irrigation, regression analyzes were performed in order to fit a mathematical model that best represents the variation yield function of nitrogen applied in melon. In the experiment which used a water depth equivalent to 1.5 times the ETc, yields were relatively larger compared with the experiment with the lowest water depth. The economic study response of melon to nitrogen for both experiments allowed identification of alternatives of nitrogen fertilizer use for greater economic return, based on plant response to N and the relationship between the price of N and melon.
Response function of melon to nitrogen doses for two irrigation levels
Keywords: Cucu mismelo L.; Nitrogen; Yield